Prospective Hybrid Molecules with Dual Anti-Viral and Anti-Thrombotic Activity Against the SARS-CoV-2 Infection and Its Associated Complications Employing in Silico Studies - Bhimanwar, R.; Thomas, A.; Kothapalli, L.; Godase, A.; Gandhi, S.; Chandani, S.; More, G.; Jadhav, G.; Choudhary, S. (Karagandy University of the name of academician E.A. Buketov, 2022)
Covid-19, a SARS-CoV virus-based disease, was identified in Wuhan, China, in December 2019. Initially, it was considered just an infection of the respiratory system, but due to its transmittable nature, it was declared a pandemic. A variety of treatment options were implemented, including antivirals like remdesvir, favipiravir along with vitamins and antioxidants. Further investigations revealed that the Covid-19 infection results in thrombotic cardiovascular complications, which are the major concern for the increased mortality associated with this disease. This study investigates the in Silico design of hybrid molecules with antiviral and antithrombotic properties. A docking study was performed using Autodock Vina software, and binding energies of the designed compounds were determined for papain-like protease (PDB: 3E9S) and 3-chymotrypsin-like cysteine protease (PDB: 6LU7). The docked poses and amino acids interactions were verified using Biovia Discovery studio 4.5. The binding energies of all designed compounds were compared with the standards, Compound RL1 (2-(5-(3-carbamoyl-1H-1,2,4-triazol-1-yl)-3,4-dihydroxytetrahydrofuran-2-yl)methoxy)- carbonyl)amino)(hydroxy)methyl)carbamoyl)phenyl acetate) and Compound FL2 (8-hydroxy-2-(3-hydroxy- 4-methoxyphenyl)-4-oxochroman-6-yl(2-(6-flouro-3-oxo-3,4-dihydropyrazine-2-carboxamido)-1-hydroxy-3- phenylpropyl)carbamate) proved to be promising agents with strong binding interactions. Hybrid molecules that inhibit viral replication, possibly as transition state inhibitors, can be investigated further for use in the treatment of SARS-Co-V infection and its associated complications.
SARS-CoV-2 инфекцияларына және онымен байланысты асқынуларға қарсы қос антивирустық және антитромботикалық потенциалы бар әлеуетті гибридті молекулалар in silico зерттеулерін қолдану
Потенциальные гибридные молекулы с двойным противовирусным и антитромботическим действием против инфекции SARS–CoV–2 и связанных с ней осложнений с использованием исследования in silico
Keywords: COVID-19; CL-pro; PL-pro; antiviral; antithrombotic; molecular docking; in Silico; hybrid molecule